Lysimachia xishuiensis, a new species of Primulaceae from the Danxia landform Guizhou, China - Wang, Xiao; Zhou, Mei; Luo, Kang; He, Baiqiu; Mu, Jun; Bai, Xinxiang (Phytotaxa, 2026)
Lysimachia xishuiensis, a new species of Primulaceae is described from the Danxia landform of Xishui County, Guizhou Province, China based on morphological differentiation at the population level and a distinct ecological niche. The new species is related to L. paridiformis and L. sciadantha, but it is readily distinguished by its diagnostic combination of well-developed stolons, slender and diminutive erect shoots, longer pedicels, and fewer flowers. The detailed color photographs and line drawings of the new species are also provided.